Perencanaan Taman Islam pada Lansekap Islamic Center Provinsi NTB - WALIDAEN, MOHAMMAD BIRRUL; UTAMI, NI WAYAN FEBRIANA; YUSIANA, LURY SEVITA (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017DO - 10.24843/JAL.2017.v03.i01.p09, 2017)
ABSTRACT Islamic Garden Planning at West Nusa Tenggara (NTB) Islamic Center West Nusa Tenggara (NTB) is one of province in Indonesia with majority of Muslim population. In consequence, it required to provide facility such as Islamic center. NTB Islamic Center was built as a center of Islamic studies and support the halal tourism in NTB. Currently, NTB Islamic Center is under construction and the landscape need to be planned in order to complete the overall construction. The aims of this study were to identify character of the landscape, to analyze any potential and obstruction at the site, and to plan the landscape of NTB Islamic Center with the Islamic garden concept. The method used in this research were literature study and field survey. Literature study was applied to get the formulation of the Islamic garden concept from Al-Qur’an and Hadith and the other literature related to Islamic garden. Furthermore, field survey was applied to determine some obstacles and the potentials of the site to support the NTB Islamic Center planning. The synthesis of study was applied as a concept to develop NTB Islamic Center. The concept of Islamic gardens was selected as a model of beauty of paradise as described in the Al-Qur’an and Hadith. Some adjustment were implemented in the site to conform its character and condition. The final result of this research was NTB Islamic Center site plan with emphasized on Islamic religion and culture. Keywords: Islamic garden, Islamic center, landscape planning, West Nusa Tenggara (NTB)